Beta-Blocker widrawal in chronic hearth failure a retrospective cross-sectional study in Manila. - Cajigas, Gian Adrian P.; Alcantara, Celeste Carmelle D.; Ayran, Charles Mandy G.; Deliza, Krystelle Kim M.; Reyes-Abaya, Rubina G. (Manila Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2025)
The beta-blocker rebound phenomenon resulting from abrupt discontinuation presents significant clinical concerns, particularly due to the potential emergence of withdrawal symptoms. Despite this risk, there remains a lack of clear, standardized guidelines on appropriate tapering strategies in current clinical practice. This study aimed to evaluate the association between various beta-blocker deprescribing strategies and the occurrence of withdrawal symptoms among adult patients with chronic heart failure, while also describing patient demographics and deprescribing characteristics.

This retrospective cross-sectional study reviewed patient charts from the Philippine General Hospital’s RADISH system, covering the period from January 2020 to June 2024. Of the 1,006 charts screened, 227 patients met the eligibility criteria, resulting in 346 deprescribing cases, as some patients underwent more than one strategy. The WHO-UMC Causality Assessment Tool was utilized to evaluate the link between deprescribing methods and withdrawal symptoms. Data were analyzed using descriptive statistics, including the Chi-squared test and Fisher’s exact test. The sex distribution was nearly equal, with 52% male and 48% female. Withdrawal symptoms occurred in 15% of cases, commonly presenting as angina, rebound hypertension, and tachycardia.

Carvedilol was used in 67% of deprescribing cases. Among the strategies employed, abrupt discontinuation was most common (49%), followed by switching (33%) and tapering (18%). Withdrawal symptoms were most frequently observed in cases of abrupt discontinuation (18%), followed by switching (13%) and tapering (10%). Higher withdrawal rates were particularly associated with switching from short-acting to long-acting beta-blockers (24%) and with larger dose reductions, especially in the 75–99% reduction group (20%). These results emphasize the widespread use of abrupt discontinuation and its link to increased withdrawal symptoms, reinforcing the need for structured deprescribing protocols to help minimize adverse outcomes in patients with chronic heart failure.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, July 2025
Keywords: Beta-adrenergic blocking agents -- Discontinuation -- Heart failure -- Philippines; Heart failure -- Drug withdrawal -- Retrospective studies -- Philippines